STRATEGI KOMUNIKASI GURU DALAM PENDIDIKAN KARAKTER - Veny Purba; Maya Retnasary; Annisa P Nurfadhillah (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
Character education is important in the present given the rapid development of times can change the character of children to be backward. This research uses descriptive qualitative method by collecting field data and this research determines the subject of the research object by referring to interview guidelines for conducting interviews and observations. The result of this study indicate that character education in class 2 TKJ 2 always prioritizes approaches to be open to each other. So the teacher can easily understand the character of wild and deep children, and it is easy to be influenced towards a better direction. This research has implications for the school to pay attention to the character of their students and make changes more aggressively and shouldn’t break up communication with students and parents when outside teaching and learning activities, must continue to evaluate with parents, so student can help each other in educate the child’s character in a better direction.